2023
DOI: 10.1088/1361-6668/acba4d
|View full text |Cite
|
Sign up to set email alerts
|

First performance test of FeSe0.5Te0.5 coated conductor coil under high magnetic fields

Abstract: Iron-based superconductors (IBS) have attracted intense interest from scientists around the world. The first FeSe0.5Te0.5 hybrid coil including one FeSe0.5Te0.5 single pancake coil (SPC) and eight YBCO double pancake coils (DPCs) was successfully fabricated and test in this study. The FeSe0.5Te0.5 tape used in the hybrid coil is encapsulated strengthen tape which is with 0.15 mm thickness and 10.5 mm width to withstand the high stress during the cold test. The FeSe0.5Te0.5 encapsulated tape exhibits good perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The high current carrying capacity of a 100 m long superconducting tape in a field was also verified through the testing of an IBS racetrack coil in 10 T [7]. Other studies related to ironbased superconducting coils have also been reported [8][9][10].…”
Section: Introductionmentioning
confidence: 69%
“…The high current carrying capacity of a 100 m long superconducting tape in a field was also verified through the testing of an IBS racetrack coil in 10 T [7]. Other studies related to ironbased superconducting coils have also been reported [8][9][10].…”
Section: Introductionmentioning
confidence: 69%
“…In 2023, Wei et al prepared a hybrid coil consisting of one 3.5-turn FeSe 0.5 Te 0.5 SP coil and eight 14-turn YBCO DP coils. The I c value of the FeSe 0.5 Te 0.5 SP coil is 17.4 A at 4.2 K and 10 T, which is almost the same performance as the short FeSe 0.5 Te 0.5 tape [31].…”
Section: Introductionmentioning
confidence: 72%
“…In the paper, Wei et al [25] reports on the first fabrication and test of a coil made from FeSe 0.5 Te 0.5 coated conductor tapes. The FeSe 0.5 Te 0.5 coated conductor was fabricated on the CeO 2 buffered IBAD-MgO metal tapes by Shanghai Jiao Tong University.…”
mentioning
confidence: 99%